2021
DOI: 10.30636/jbpa.42.220
|View full text |Cite
|
Sign up to set email alerts
|

Public support for ‘soft’ versus ‘hard’ public policies: Review of the evidence

Abstract: This article reviews the literature on public support for ‘soft’ versus ‘hard’ policy instruments for behaviour change, and the factors that drive such preferences. Soft policies typically include ‘moral suasion’ and educational campaigns, and more recently behavioural public policy approaches like nudges. Hard policy instruments, such as laws and taxes, restrict choices and alter financial incentives. In contrast to the public support evidenced for hard policy instruments during COVID-19, prior academic liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…The results of our ROL regression indicated that public managers are relatively willing to use behavioral policy instruments, particularly in comparison to the use of financial and material incentives. These results confirm earlier studies on the relative acceptance of the use of behavioral policy instruments (Reisch & Sunstein, 2016;Sunstein et al, 2018Sunstein et al, , 2019Banerjee et al, 2021), but now from the perspective of senior public managers. Behavioral policy instruments are relatively low cost (Benartzi et al, 2017) and can be used to pursue policy objective without the political costs of additional regulations, bans and oversight.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The results of our ROL regression indicated that public managers are relatively willing to use behavioral policy instruments, particularly in comparison to the use of financial and material incentives. These results confirm earlier studies on the relative acceptance of the use of behavioral policy instruments (Reisch & Sunstein, 2016;Sunstein et al, 2018Sunstein et al, , 2019Banerjee et al, 2021), but now from the perspective of senior public managers. Behavioral policy instruments are relatively low cost (Benartzi et al, 2017) and can be used to pursue policy objective without the political costs of additional regulations, bans and oversight.…”
Section: Discussionsupporting
confidence: 89%
“…Second, we assessed public managers' support for the use of behavioral policy instruments, but in relation to other relevant policy instruments. This way, we go beyond the standard binary questions (yes/no: support/no support) and offer a more ecologically valid and realistic measure of individual preferences and opinions about the use of behavioral policy instruments (Gideon, 2012;Davidai & Shafir, 2020;Banerjee et al, 2021). Third, we identified several factors informing administrative support for the use of behavioral policy instruments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…al., 2010; and it is therefore reasonable to expect that genetics affects administrative phenomena at least through its effects on the political sphere. First, as the BPA literature is also concerned with studying what makes citizens accept different types of policies (Banerjee, Savani, & Shreedhar, 2021) and support government programs (Nicholson-Crotty, Miller, & Keiser, 2021) it may be fruitful to incorporate BG methods to strengthen the explanatory models of policy approval within BPA. Secondly, bureaucracies are naturally politically governed institutions, and the effects of political decisions will invariably spill over into the implementation phases thereby affecting classic BPA phenomena.…”
Section: Insights From Behavioral Geneticsmentioning
confidence: 99%